2018
DOI: 10.22159/ijpps.2018v10i5.24748
|View full text |Cite
|
Sign up to set email alerts
|

HPTLC Method for the Determination of Lupeol From Andrographis Echioides Leaves

Abstract: Objective: A new simple, precise, rapid and selective high -performance thin-layer chromatographic (HPTLC) method has been developed for th e determination of lupeol in methanolic leaves extract of Andrographis echioides leavesResults: The retention factor of lupeol was found to be 0.55. Linearity was obtained in the range of 5000 ng -10000 ng for lupeol. The developed and validated HPTLC method was employed for lupeol in methanolic leaves extract of Andrographis echioides for standardization of the content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The reductors lend electron to the radicals and thereby cease the radical chain reaction forming stable compounds. The study revealed that the extract possesses similar reducing power compared with ascorbic acid as standard [25].…”
Section: Discussionmentioning
confidence: 89%
“…The reductors lend electron to the radicals and thereby cease the radical chain reaction forming stable compounds. The study revealed that the extract possesses similar reducing power compared with ascorbic acid as standard [25].…”
Section: Discussionmentioning
confidence: 89%
“…Previously some methods were reported on Bauhinia plant species but they have reported some other compounds such as syringic acid, vanillic acid, caffeic acid, and kaempferol (Gupta et al, 2015. Some studies have been reported on quantification of lupeol by HPTLC, but the chemical compound was obtained from different species, such as Ficus (Rathee et al, 2015), Andrographis echioides leaves (Gurupriya et al, 2018; Kumar Ettaboina et al, 2022), and Alstonia scholaris (Ettaboina & Nakkala, 2021; Sanaye & Zehra, 2019). Although lupeol from various species was quantified using different HPTLC methods, not much data on the quantification of lupeol from Bauhinia species are available.…”
Section: Resultsmentioning
confidence: 99%
“…HPTLC studies of methanolic sample extract for identification of stigmasterol, quercetin, and kaempferol simultaneously in Indigofera tinctoria and quantification of kaempferol and quercetin in various medicinal plants has been performed [14,15]. Isolation and identification of stigmasterol and β-sitosterol through HPTLC from methanolic extract of root bark of Calotropis gigantea and quantification of stigmasterol and lupeol from Ficus religiosa [16,17] and lupeol from Andrographis echioides leaves has been done [18]. These types of quantification studies thus stand useful in suggesting a wide array of possible therapeutics from natural sources.…”
Section: Resultsmentioning
confidence: 99%